Accommodations and academic performance: First-year university students with disabilities - Parsons, Jeanette; McColl, Mary Ann; Martin, Andrea K.; Rynard, David W. (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2021)
Despite growing enrollment of university students with disabilities, they have not achieved academic parity with their non-disabled peers. This study matched 71 first-year university students with disabilities and students without disabilities on three variables: high school average when admitted to university, gender, and program of study. Both groups of students were compared on three measures of academic performance: GPA, failed courses, and dropped courses after first year of university. The relationship between accommodations and academic performance was also analyzed for students with disabilities. Evenwhen matched on admission average, gender, and program of study, students with disabilities had a significantly lower GPA and were more likely to fail courses in their first year than their peers without disabilities. While note-taking in the classroom was associated with being less likely to drop a course, it was also associated with poorer academic performance, as was using a calculator or alternate format during exams. The more accommodations students lost in the transition from high school, the worse they performed academically at university. Students who lost human assistant support in the classroom and theuse of a computer or a memory aid during exams had a significantly lower GPA and were more likely to fail courses in their first year of university compared with students who did not lose these accommodations. These findings have implications for accessibility offices and universities in supporting the access needs and academic success of students with disabilities.